MEDIA CONSUMPTION BEHAVIOUR OF YOUNG INDONESIAN EXECUTIVES: SEARCHING FOR OPPORTUNITIES FOR CONVENTIONAL MEDIA TO EXIST - Amalia E. Maulana (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The purpose of this study is to investigate how young executive audience interacts with both conventional and contemporary media in their daily life. Although it has not played as the dominant source of information and entertainment due to high competition from digital media, this study found that conventional media still have a place in the life of this audience. Interestingly, in situations where online media is consumed in a continuous manner, the complementary of conventional media such as printed and electronic remains a necessity. This research finds that it is very important for media managers to acknowledge the differences in needs within a certain period or a particular moment associated with the benefit sought. Through ethnography study, it revealed that difference in media choices are also determined by situational behaviours such as (1) Work-driven vs. Self-driven needs; (2) Passive Content Search vs. Active Content Search; (3) Speed/Urgency vs. Profoundness of content; (4) Work-related vs. Lifestyle-related content; and (5) Mobile vs. Static. This finding contributes in widening the perspective of conventional media managers about the way to survive in an increasingly narrow market.